2021
DOI: 10.1007/s40520-021-01850-x
|View full text |Cite
|
Sign up to set email alerts
|

Carotid intima-media thickness in patients with hyperuricemia: a systematic review and meta-analysis

Abstract: Objective Despite the high incidence and mortality of cardiovascular events in hyperuricemia patients, the role of serum uric acid in cardiovascular diseases is still controversial. The aim of this meta-analysis was to explore the difference of carotid intima-media thickness in hyperuricemia and control groups. Methods We performed this meta-analysis by searching the PubMed, Cochrane Library, Embase and Web of Science databases up to July 2020. The 95% confidence intervals and standard mean differences were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Similarly, several studies reported that SUA levels were independently associated with the development of cardiovascular and cerebrovascular diseases, especially myocardial infarction and stroke; therefore, SUA is a strong predictor of subsequent cardiovascular diseases and all-cause death ( 20 – 23 ). The result of a recent meta-analysis showed that patients with hyperuricemia had a higher incidence of CIMT thickening than the normal population ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, several studies reported that SUA levels were independently associated with the development of cardiovascular and cerebrovascular diseases, especially myocardial infarction and stroke; therefore, SUA is a strong predictor of subsequent cardiovascular diseases and all-cause death ( 20 – 23 ). The result of a recent meta-analysis showed that patients with hyperuricemia had a higher incidence of CIMT thickening than the normal population ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…While cfPWV is a gold standard for measuring arterial function, CIMT, on the other hand, mainly represents the structure of the carotid artery [ 13 ]. Studies have shown a large age impact on the relationship between SUA and CIMT [ 34 , 35 , 36 ]. Nevertheless, in this study we had a different age range between the men and women groups; however, we did not succeed in finding an association in either of them.…”
Section: Discussionmentioning
confidence: 99%
“…The uric acid/creatinine ratio (Uric/Cr) decreased from 8.86 ±2.49 preoperatively to 7.90 ±2.74, 7.6 ±2.29, and 6.92 ±1.86 at 1, 3, and 6 months after surgery (P =0.025)(see Table 5 and Figure 2). [20,21], additionally, lowering uric acid levels may reduce cardiovascular events in patients with sleep apnea [22]. Previous studies suggested that obstructive sleep apnea syndrome may be a potential risk factor for the development of hyperuricemia and gout [4].…”
Section: Diagnostic Potential Of Bmi On Hyperuricemia In Obesity With...mentioning
confidence: 99%